Gendered constitution building process for Syria: report. Gender entry points to a democratic constitution in syria and lessons learned from constitution making processes in the Middle east and North Africa (Paris, 2014)
"The report provides gender entry points to a democratic constitution in Syria and lessons learned from constitution making processes in the MENA region. It is a result of several months of collaborative work of the Coalition of Syrian Women for Democracy, bringing together diverse groups of Syrian activists, mobilized for a constitution building process to support a non-violent transition towards democracy. The report integrates the results of those numerous events, gatherings and discussions. It draws attention to challenges and highlights good practices related to the institutionalization of women’s rights and gender equality principles and values in the constitution. It also emphasizes the efforts of women’s movements to include and/or preserve women’s rights and gender equality as founding principles in democratic constitutions, and as core issues in times of transition. It underlines the role of progressive men in the work towards the institutionalization of gender equality."